The good housekeeping illustrated book of pregnancy baby care - Levine, Ellen (Hearst Books, 1999)
This book offers a comprehensive look at all stages of pregnancy and the first three years of child's life, including updated lists of essential medical testas during pregnancy, growth and weight charts, and immunization schedules.